Manfaat dan Metode Aplikasi Sensus Penduduk Online di Desa Sukabakti - Tri Dharma Putra; Rakhmat Purnomo (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Census is the calculation of the total population, economy, etc. conducted by the government within a period of time, carried out simultaneously, and is comprehensive within a country boundary for the interests of the country's demographics concerned. At present Sukabakti village in Tambelang sub-district, Bekasi Regency does not have accurate data population. It is estimated that there are around 8000 residents in this district. However, there are many people who do not have a ID card (KTP), so they are not registered. Their reason is because they do not feel they need a ID card because it is useless. The large number of unregistered people requires manual data collection. This is where a census population is needed for the people of this village. There are several methods for conducting population censuses. In practice, the recording method or census used can be divided into two, namely the householder method and the canvaser method. Based on the status of residence of the population, the census can be divided into the de facto census and the de jure census. With the development of digital technology and information systems, the census can be done by online applications. This journal will discuss these methods so as to increase the knowledge of us about the population census and its application by using an online census application.